1985
DOI: 10.1111/j.1348-0421.1985.tb00899.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation in Mice by Experimental Infection with Yersinia enterooolitica

Abstract: Intraperitoneal infection of mice with two strains of Yersinia enterocolitica resulted in an inflammatory response and immunomodulation which appeared to be related to the invasive properties of the bacteria.The primary antibody response to sheep erythrocytes was enhanced by noninvasive cultures of Y. enterocolitica (serotype the same time or two days after the antigen (invasiveness was tested on HeLa cells). In contrast, invasive cultures of serotype O :3 grown at 22 C, injected three days before the antigen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…with 5 )< 107 bacteria in 0.1 ml saline [9]. Experimental groups comprised at least 6 mice of 6-8 weeks of age.…”
Section: Mice and Experimental Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…with 5 )< 107 bacteria in 0.1 ml saline [9]. Experimental groups comprised at least 6 mice of 6-8 weeks of age.…”
Section: Mice and Experimental Infectionmentioning
confidence: 99%
“…Mice were killed 24 h after the eliciting treatment, and peritoneal cells were harvested as described previously [9], except that Hanks' solution with sodium heparinate was used; peritoneal leukocytes were counted in a hemocytometer chamber.…”
Section: Peritoneal Leucocyte Responsementioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that low‐virulence Y. enterocolitica strains possess immunomodulatory properties [7–9]. Interestingly, experimental infection with IP383, a pYV‐bearing strain belonging to the low‐virulence serotype O9, confers on BALB/c mice significant resistance levels against transplantation of the syngeneic lymphoma LSTRA or challenge with a lethal dose of the intracellular pathogen Listeria monocytogenes [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of experimental yersiniosis on immunity parameters, such as the size of spleen cell subsets or the production of immune cytokines, have been documented in mice infected with serotype O8 strains (Autenrieth et al., 1994 ; Bohn et al, 1998). In comparison, lowvirulence serotypes have received little attention, although they possess immunomodulatory properties (Ruiz-Bravo et al, 1985. In humans, enteric colonization with low-virulence serotypes may persist for periods of up to 14 weeks without symptoms (Morris et al, 1991) ; however, there is no information available about the possible effects of the intestinal carriage of these strains on the immune condition of the hosts.…”
Section: Introductionmentioning
confidence: 99%